Research utilization competency development in the health workforce pipeline: Design and formative evaluation of learning objectives for health professions students - Olive W. Yini Karway; Jeremiah Wleh; Yamah Kpatakolee; Joseph Sieka; Neima Candy; Kristina Talbert-Slagle; Bernice T. Dahn; Wahdae-Mai Harmon-Gray; Laura A. Skrip (Health Research Policy and Systems)
Abstract Background It is widely recognized that use of research evidence to guide health policy and practice could lead to adoption of life-saving interventions and more effective resource allocation. However, the skills around research utilization are often assumed and rarely taught, particularly in low- and middle-income country contexts. Here we present a set of competency areas and learning objectives developed for institutionalization of research utilization across health professions schools in Liberia. Ahead of implementation and to gauge their perceived value and utility, a participatory formative evaluation was undertaken. Methods Focus group discussions were held to gain feedback on a set of research utilization learning objectives and the proposed implementation approach. Focus group participants were drawn from faculty and students at the University of Liberia College of Health Sciences (ULCHS), which houses the country’s only medical and pharmacy schools, along with schools of public health and nursing and midwifery. ULCHS serves an essential role in the health workforce pipeline. Results Findings from the focus group discussions identified a limited understanding of research utilization at the ULCHS but a demand for stronger understanding of research methodology and evidence. Participants identified clear examples of how the skills represented in the learning objectives could help specifically their personal careers as well as more broadly the health sector of Liberia. Potential challenges were noted around the incorporation of research utilization learning objectives into existing courses and tended to be logistical (for example, poor internet connectivity and low digital literacy) or around lack of foundational understanding and skills (for example, lack of experience with literature searches and reviews). However, the approach was generally perceived as contextually aware since it would not add new courses, which come with credit fees and extra time commitment, and would focus on practical skills-building rather than theoretical content. Conclusions Integrating research utilization learning objectives into existing curricula in health professions schools is expected to enhance uptake and application of research evidence in the Liberian health sector, as students emerge from the workforce pipeline to fill positions in clinical and policy settings. The success of the approach will warrant ongoing evaluation, along with mentorship of faculty, to increasingly incorporate skills and content of local relevance into courses.